Interaction of the major inflammatory bowel disease susceptibility alleles in Crohn's disease patients - Csöngei, Veronika; Járomi, Luca; Sáfrány, Eniko; Sipeky, Csilla; Magyari, Lili; Faragó, Bernadett; Bene, Judit; Polgár, Noémi; Lakner, Lilla; Sarlós, Patrícia; Varga, Márta; Melegh, Béla (World journal of gastroenterology : WJG, 2010)
To investigate the interaction of interleukin-23 receptor (IL23R) (rs1004819 and rs2201841), autophagy-related 16-like 1 (ATG16L1) (rs2241880), caspase recruitment domain-containing protein 15 (CARD15) genes, and IBD5 locus in Crohn's disease (CD) patients. A total of 315 unrelated subjects with CD and 314 healthy controls were genotyped. Interactions and specific genotype combinations of a total of eight variants were tested. The variants of IBD5 locus (IGR2198a_1 rs11739135 and IGR2096a_1 rs12521868), CARD15 (R702W rs2066845 and L1007fs rs2066847), ATG16L1 (rs2241880) and IL23R (rs1004819, rs2201841) genes were genotyped by PCR-RFLP, the G908R (rs2066844) in CARD15 was determined by direct sequencing. The association of ATG16L1 T300A with CD was confirmed [P = 0.004, odds ratio (OR) = 1.69, 95% CI: 1.19-2.41], and both IL23R variants were found to represent significant risk for the disease (P = 0.008, OR = 2.05, 95% CI: 1.20-3.50 for rs1004819 AA; P < 0.001, OR = 2.97, 95% CI: 1.65-5.33 for rs2201841 CC). Logistic regression analysis of pairwise interaction of the inflammatory bowel disease (IBD) loci indicated that IL23R, ATG16L1, CARD15 and IBD5 (IGR2198a_1) contribute independently to disease risk. We also analysed the specific combinations by pair of individual ATG16L1, IL23R rs1004819, rs2201841, IGR2198a_1, IGR2096a_1 and CARD15 genotypes for disease risk influence. In almost all cases, the combined risk of susceptibility pairs was higher in patients carrying two different risk-associated gene variants together than individuals with just one polymorphism. The highest OR was found for IL23R rs2201841 homozygous genotype with combination of positive CARD15 status (P < 0.001, OR = 9.15, 95% CI: 2.05-40.74). The present study suggests a cumulative effect of individual IBD susceptibility loci.